ANXIETY AND UNCERTAINTY MANAGEMENT: LIGHTS AND SHADOWS OF INTERNATIONAL STUDENTS IN INTERCULTURAL COMMUNICATION AT DIPONEGORO UNIVERSITY IN SEMARANG - Silas Hamenyimana; Hapsari Dwiningtyas Sulistyani; Turnomo Rahardjo (Interaksi: Jurnal Ilmu Komunikasi, 2023)
The aim of this study is to explore and interpret the significant challenges experienced by international students and the strategies used to cope with them in managing their anxiety and uncertainty in intercultural communication settings at Diponegoro University. A sample size of five students was purposively selected and participated in the data collection using in-depth and semi-structured interviews. The data were analyzed qualitatively using Interpretative Phenomenological Analysis. Through their lived experiences, we realized that majority of participants were clueless about the Indonesian language and Indonesia/ Javanese culture in which some of them faced anxiety and uncertainty challenges in their arrival et during their initial interaction, and adaptation process challenges based chiefly on language anxiety and uncertainty; new culture and environment in communication and interaction with the inside and outside the campuses. They coped with their anxiety and uncertainty by accepting host culture’s lifestyle, friendships, learning the Indonesian language, attending prayers at Mosques, hanging out with friends, and self-learning. Additional learning materials such as dictionaries, google translate, watching the news, books, family assistance, and listening to music were added to overcome their linguistic anxiety and uncertainty. The motivation from lecturers, classmates, and local people to learn a new language was valuable.